2018
DOI: 10.1073/pnas.1719663115
|View full text |Cite
|
Sign up to set email alerts
|

Rapid selection of a pyrethroid metabolic enzyme CYP9K1 by operational malaria control activities

Abstract: SignificanceEliminating malaria from islands should, in theory, be easier than eliminating malaria from countries in mainland Africa because of restricted movement of insects and people between treated and untreated areas. The example of Bioko Island, where the entomological inoculation rate in 2004 was among the highest in Africa, demonstrates how difficult this can be. Vector control has eliminated two of the four vector species, and malaria has been dramatically reduced. This study demonstrates rapid evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 47 publications
4
96
0
Order By: Relevance
“…Finally, Cyp9k1 was the most widely amplified gene of the five, with CNVs found in over half of the populations in our dataset. Cyp9k1 is up-regulated in mosquitoes resistant to pyrethroids and DDT [44,45,48], and metabolises deltamethrin [35]. Furthermore, a selective sweep in the Cyp9k1 region has been associated with insecticide resistance in An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Cyp9k1 was the most widely amplified gene of the five, with CNVs found in over half of the populations in our dataset. Cyp9k1 is up-regulated in mosquitoes resistant to pyrethroids and DDT [44,45,48], and metabolises deltamethrin [35]. Furthermore, a selective sweep in the Cyp9k1 region has been associated with insecticide resistance in An.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae and An. coluzzii, the most import metabolic genes that have been identified as major insecticide resistance candidates to date are Gste2 [28], Cyp6p3 [29,30], Cyp6m2 [29,31,32], Cyp6z1 [33] and Cyp9k1 [34,35]. If…”
Section: Introductionmentioning
confidence: 99%
“…We found two sweeps on insecticide-related genes that are common targets of selection elsewhere but which have incompletely colonized the Ssese Islands: one on cytochrome P450 monooxygenase Cyp9K1 [44, 45] present on some islands, and another on glutathione Stransferase genes ( Gste1-Gste7 ; [4649]) at extremely low frequency on the islands. That the selective sweeps targeting these loci [4] have not fully colonized the islands despite the advantage in detoxifying pyrethroids and DDT suggests a lack of contemporary exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of insecticides in the environment include the application of insecticide-based vector control interventions for public health, such as LLINs and IRS, and the application of agricultural insecticides, which include the same insecticide classes as those used in vector control 11 . Several studies have demonstrated a local increase in insecticide resistance in field mosquito populations following the implementation of LLINs, IRS, or both 12, 13, 14, 15, 16 although in other locations evidence of higher resistance after the introduction these interventions was not found 12, 17 . Associations between agricultural pesticide use and insecticide resistance have also been found 11, 18 , and there is evidence that pesticide contamination of water bodies is a source of selection pressure for resistance acting on mosquito larvae 19 .…”
Section: Introductionmentioning
confidence: 99%